Framework para implementação do lean healthcare na manutenção hospitalar - Michelon, Eden Carlos (2022)
The Lean methodology and its tools and practices incorporate quality assurance, cost and waste reduction and the reorganization of work in its base, in the health area the adaptation of the methodology was called Lean Healthcare, and its development is highlighted in the improvement of hospital management. Hospital maintenance, as well as maintenance in the industrial and service segments, has as its main purpose the availability and reliability of equipment and facilities, serving as an operational base for all sectors. The Lean methodology when implemented in maintenance aims to eliminate waste and improve performance, seeking customer satisfaction, with services performed through lower costs, more agility and high quality. The objective of this work was to develop a framework that makes it possible to assist the implementation of Lean Healthcare in hospital maintenance. Initially, a literature review sought to identify issues related to the existence of the application of the Lean Healthcare methodology in hospital maintenance. The development of the framework was carried out through the combination of two methodologies identified in the literature, both focused on maintenance, one developed for the applicability of Lean Maintenance and the other for the management of hospital maintenance. A framework was developed that guides the implementation of Lean in the maintenance sector in medium-sized hospitals. A hospital located in the southwest region of Paraná was the object of the study, which allowed the perception of the applicability of the framework, and the Lean methodology tools to be used, such as flow map, 5S, FMEA, Kaizen and Kanban. Hospital maintenance professionals evaluated the development of the study, and also presented their considerations about the Framework and Lean Healthcare.